Satisfacción laboral del personal de enfermería y su relación con la calidad del cuidado al usuario en el servicio de medicina en los Hospitales II-2 Minsa y ESSALUD -Tarapoto, Agosto- Diciembre 2015 - Alarcón Adrianzén, Gaby Mirian (2015)
This study entitled "Job satisfaction of nurses and their relationship to the quality of care the user in the medical service in hospitals II-2 MINSA and ESSALUD - Tarapoto, August-December 2015"; was quantitative, descriptive, comparative type of transversal, prospective court. The sample universe was represented by 13 nurses, seven nurses MOH Hospital, 6 nurses of ESSALUD Hospital and 158 users in the health service, with 84 users and 74 MOH Hospital ESSALUD Hospital. Two questionnaires, the first was used to measure job satisfaction of nurses and the second to measure the quality of care the user in the medical service. Applied through the survey technique. Among its findings was obtained in the ESSALUD Hospital; 83.5% of nurses presented average job satisfaction, followed by 16.7% in low level. With respect to MINSA hospital, 57.1% had average job satisfaction, followed by 28.6% in low level, as averaged over the ESSALUD Hospital with job satisfaction MEDIA downward trend in higher percentages compared MOH Hospital. With regard to the quality of care to the user; 67.6% of users expressed ESSALUD MEDIA quality care. In the MOH Hospital 63.1% reported MEDIA quality care. Chi square results show a significance level of p> 0.05, indicating no relationship between two variables.